Error Analysis of Indonesian Grammatical Interference in Students‘ English Composition - Puspita (P2M Politeknik Pertanian Negeri Samarinda, 2021)
The first language (L1) of learners has a significant effect in learning a foreign language. The influence of L1 could become errors, that is called interference. The main purposes of the study are to identify the most dominant type of language interference and the factors contribute to language interference in students’ English composition. The data were collected from 67 Second Grade Students of Plantation Management Study Program in State Polytechnic of Agriculture, Samarinda for the Academic Year 2019/2020, and taken through elicitation technique and documentation, and then analyzed the errors. The result of the study shows that the type of grammatical interference comprise morphological errors and syntactical errors were the most troublesome areas of language that students encountered when conducting composition in English. Since the main focus of the study is L1 interference, only errors related to Indonesian as L1 interference were addressed.